THE INFLUENCE OF CONVENIENCE, TRUST, AND SECURITY ON PAYLATER USAGE (A CASE STUDY ON GEN Z IN SIDOARJO) - Gracilla Aisya Adi Utomo; Sriyono Sriyono (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the influence of convenience, trust, and security on Generation Z’s decisions to use Paylater services in Sidoarjo. Method: A quantitative research design was employed using a survey method distributed to Generation Z respondents to assess factors influencing their adoption of Paylater services. Results: The findings show that convenience, trust, and security each have a positive and significant effect on users’ decisions to use Paylater. This suggests that ease of access, confidence in the service provider, and perceptions of transaction safety play essential roles in shaping adoption behavior. The results also reinforce previous research highlighting that favorable perceptions of convenience, trust, and security are key determinants in the acceptance of financial technology. Novelty: This study contributes to the growing body of literature on digital financial behavior by providing empirical evidence on Generation Z’s Paylater usage patterns in Indonesia, emphasizing the importance of user trust and perceived security in sustaining fintech adoption.